SOCIO-PEDAGOGICAL CONDITIONALITY OF IMPLEMENTATION DIFFERENTIATIONS IN MODERN EDUCATION (Pedagogy of Higher and Secondary Education, 2022)
Differentiation of teaching as educational technology at general school on this stage of development of our society is predefined: by the attempt of society more rationally to use potential possibilities of everybody, that is related to maximal development of the natural making and skills of students; by the anxiety of society about comprehensive and harmo nious development of personality; by the necessity of subsequent perfection of work of gen eral school.
Keywords: 1